Energy-efficient communication in multihop wireless sensor networks using ternary encoding and silent symbols. (1st January 2013) - Ghosh, Rabindranath; Sinha, Koushik; Datta, Debasish; Sinha, Bhabani P.
The ternary-with-silent-symbol (TSS) energy-efficient data communication technique was earlier proposed in Ghosh et al. (2008) which coupled ternary encoding of data stream with the use of silent periods for transmitting the ternary digits. The performance analysis of TSS using bit-error rate (BER), however, is inadequate to capture the transitive error-propagation in the transmitted binary data stream. In this paper, we use the concept of frame-error rate (FER) to successfully capture the effects of the error-propagation and the message length reduction. Our FER-based analysis shows 23% average saving in transmitter energy compared to the non-coherent BFSK for AWGN channels, rather than 20% saving as in BER-based analysis. For coherent detection-based receiver we show that the average transmitter energy savings are about 30% and 17% relative to the non-coherent and coherent BFSK respectively. Simultaneously, there is energy saving of about 37% in the receiver relative to BFSK, which makes TSS a very suitable scheme for multihop communication in wireless sensor networks.